La tragedia della pace - Ferrero, Guglielmo, 1871-1942 (Salt Lake City, UT : Project Gutenberg, 2025)
"La tragedia della pace : Da Versailles alla Ruhr" by Guglielmo Ferrero is a collection of political essays and historical analysis written in the early 20th century. The work probes the European settlement after the First World War, arguing that the collapse of old monarchies left a vacuum of legitimacy filled by raw force, punitive passions, and contradictory aims. It scrutinizes Versailles through themes such as reparations, disarmament, shifting borders, and the stillborn promise of the League of Nations, contrasting Wilson$1 (Bs idealism with Clemenceau$1 (Bs power politics. The book$1 (Bs likely focus is how a peace made without clear principles risks perpetuating conflict from France to the Ruhr. The opening of this work sets out Ferrero$1 (Bs thesis: the war ended in the ruin of Europe$1 (Bs monarchical order, but the victors, driven by ressentiment and the (3z(Bchimera of unlimited power,(3y (Bfailed to replace it with sound principles, leaving force to rule where authority had died. In (3z(BLe baionette e l$1 (Bidea(3y (Bhe calls the war (3z(Bmillions of bayonets seeking an idea,(3y (Bwarning that 1848$1 (Bs promises reappear in distorted form and that peace will be chaos unless institutions and limits are rebuilt. He critiques Clemenceau$1 (Bs reliance on armaments and alliances over true international guarantees, doubting any lasting quadruplice and urging that the pen must substitute for the sword. Reporting from Paris, he notes the obsession with reparations, the babel of clashing aims, and the peril of disarming and humiliating Germany while inventing buffer states and borders that lack consent. He labels Europe$1 (Bs statecraft a (3z(Bnew infancy,(3y (Bcontrasts Vienna$1 (Bs sober legitimacy with Napoleonic improvisation, chides Europeans for expecting endless American (3z(Bmiracles,(3y (Band closes this opening stretch by flagging the paradox of the great absentees$1 (BRussia and Germany$1 (Bwhose shadow dominates the peace. (This is an automatically generated summary.)s
Release date is 2025-07-19
Barbara Magni and the Online Distributed Proofreading Team at http://www.pgdp.net (This file was produced from images made available by the HathiTrust Digital Library)
Keywords: Paris Peace Conference (1919-1920); World War, 1914-1918 -- Peace; World War, 1914-1918 -- Influence